Plasma Exosomes at the Late Phase of Remote Ischemic Pre-conditioning Attenuate Myocardial Ischemia-Reperfusion Injury Through Transferring miR-126a-3p - Li, Danni; Zhao, Yang; Zhang, Chuyi; Wang, Fan; Zhou, Yan; Jin, Sanqing (Frontiers in Cardiovascular Medicine, 2021)
Background: Remote ischemic preconditioning (RIPC) alleviated the myocardial ischemia-reperfusion injury, yet the underlying mechanisms remain to be fully elucidated, especially at the late phase. Searching a key component as a transfer carrier may provide a novel insight into RIPC-mediated cardioprotection in the condition of myocardial ischemia-reperfusion. Objective: To investigate the cardioprotective effect of plasma exosomes at the late phase of RIPC and its potential signaling pathways involved. Methods and Results: Exosomes were isolated from the plasma of rats 48 hours after the RIPC or control protocol. Although the total plasma exosomes level had no significant change at the late phase of RIPC (RIPC-exosome) compared with the control exosomes (Control-exosome), the RIPC-exosome afforded remarkable protection against myocardial ischemia-reperfusion (MI/R) injury in rats and hypoxia-reoxygenation (H/R) injury in cells. The miRNA array revealed significant enrichment of miR-126a-3p in RIPC-exosome. Importantly, both miR-126a-3p inhibitor and antagonist significantly blunted the cardioprotection of RIPC-exosome in H/R cells and MI/R rats respectively, while miR-126a-3p mimic and agomir showed significant cardioprotection against H/R injury in cells and MI/R injury in rats. Mechanistically, RIPC-exosome, especially exosomal miR-126a-3p, activated the reperfusion injury salvage kinase (RISK) pathway by enhancing the phosphorylation of Akt and Erk1/2, and simultaneously inhibited Caspase-3 mediated apoptotic signaling. Conclusions: Our findings reveal a novel myocardial protective mechanism that plasma exosomes at the late phase of RIPC attenuate myocardial ischemia-reperfusion injury via exosomal miR-126a-3p.